A comprehensive assessment of environmental exposures and the medical history guides multidisciplinary discussion in interstitial lung disease. (April 2021) - Dodia, Neal; Amariei, Diana; Kenaa, Blaine; Corwin, Doug; Chelala, Lydia; Britt, E. James; Sachdeva, Ashutosh; Luzina, Irina G.; Hasday, Jeffrey D.; Shah, Nirav G.; Atamas, Sergei P.; Franks, Teri J.; et al.
Abstract: Background: Multidisciplinary discussion (MDD) is widely recommended for patients with interstitial lung disease (ILD), but published primary data from MDD has been scarce, and factors influencing MDD other than chest computed tomography (CT) and lung histopathology interpretations have not been well-described. Methods: Single institution MDD of 179 patients with ILD. Results: MDD consensus clinical diagnoses included autoimmune-related ILD, chronic hypersensitivity pneumonitis, smoking-related ILD, idiopathic pulmonary fibrosis, medication-induced ILD, occupation-related ILD, unclassifiable ILD, and a few less common pulmonary disorders. In 168 of 179 patients, one or more environmental exposures or pertinent features of the medical history were identified, including recreational/avocational, residential, and occupational exposures, systemic autoimmune disease, malignancy, medication use, and family history. The MDD process demonstrated the importance of comprehensively assessing these exposures and features, beyond merely noting their presence, for rendering consensus clinical diagnoses. Precise, well-defined chest CT and lung histopathology interpretations were rendered at MDD, including usual interstitial pneumonia, nonspecific interstitial pneumonia, and organizing pneumonia, but these interpretations were associated with a variety of MDD consensus clinical diagnoses, demonstrating their nonspecific nature in many instances. In 77 patients in which MDD consensus diagnosis differed from referring diagnosis, assessment of environmental exposures and medical history was found retrospectively to be the most impactful factor. Conclusions: A comprehensive assessment of environmental exposures and pertinent features of the medical history guided MDD. In addition to rendering consensus clinical diagnoses, MDD presented clinicians with opportunities to initiate environmental remediation, behavior modification, or medication alteration likely to benefit individual patients with ILD. Highlights: Multidisciplinary discussion (MDD) is endorsed for interstitial lung disease (ILD). Prior published MDD data has focused on chest CT and lung biopsy interpretations. Our MDD showed the value of assessing environmental exposures and medical history. MDD may offer opportunities for environmental, behavior, or medication modification.